Challenges of organizing non-stationary retail structures in the urban fabric of Khabarovsk - L. G. Dyachkova; Yu. V. Ordynskaya; K. S. Ilyin (Архитектура, строительство, транспорт)
This study examines the organization of retail modules and linear retail structures in Khabarovsk, that shaping public perception of accessible, high-quality goods and services. The paper considers the linear retail structures along Tikhookeanskaya Street, one of the major transportation artery connecting numerous mobile and stationary retail outlets. Employing a mixed-methods approach – incorporating comparative, cartographic, and field research – allow us to identify main features of linear retail structures, analyze key challenges in retail placement, explore planning scenarios, and examine architectural and spatial arrangements of non-stationary retail outlets that promote accessibility for city residents. The study proposes architectural solutions for existing street retail modules, such as facades made of perforated or mesh panels with decorative designs or murals. It also presents design proposals for non-stationary retail structures to enhance the city’s aesthetic appeal. One project – wrought-iron ice cream kiosks – has already been implemented, while another is a student-designed concept for a retail complex inspired by fair marquees. These solutions aim to preserve regional identity and offer a rational planning approach within the context of necessary urban densification.